If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 2 + x = -9 Reorder the terms: 2 + -2x + x = -9 Combine like terms: -2x + x = -1x 2 + -1x = -9 Solving 2 + -1x = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = -9 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = -9 + -2 -1x = -9 + -2 Combine like terms: -9 + -2 = -11 -1x = -11 Divide each side by '-1'. x = 11 Simplifying x = 11
| -46-3n=-23 | | X2-1/4=0 | | k^2+19k+60=0 | | 3x^2-90x+240=0 | | -6*-2= | | 8x+3=-2x+23 | | 5y-7x(43+6y)=-42 | | x^3-12/4=13 | | -7+3x=-40 | | (6x+7)+(3x+5)= | | 3(1+5k)=63 | | f(x)=x^2-3x-18 | | -4(-2+3m)-5m=76 | | -7+6x=53 | | -2+4p=-30 | | (X/3)-17=8 | | -2x^2+5=-2x | | 6a^2+15a=0 | | 9-4m=-5m | | .8x(x-100)=450 | | 3n^2+12n/6n | | 2x+16=76 | | -x+2(1+3)=16 | | 9y-47=y+43 | | (x/3)+2=12 | | y+3(y-1)=-11 | | (n/3)-2=14 | | 3(2-w)=12 | | 7+3a-5=14 | | 45k=0 | | (n-3)9=36 | | 105+5-4s=13 |